2005
DOI: 10.2136/sssaj2004.0239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sediment Deposition on Fine Root Dynamics in Riparian Forests

Abstract: One of the most important functions of riparian zones is their ability to improve water quality by trapping sediment leaving agricultural fields and other disturbed areas. However, few data exist quantifying the impacts of sediment deposition from anthropogenic disturbance on belowground processes within these ecosystems. This study was conducted at Ft. Benning, GA, where disturbance caused by military training has generated a range of sedimentation levels in riparian forests near ephemeral streams. Nine ephem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Microbial and plant dynamics are not well understood in these types of recent deposits. Cavalcanti and Lockaby (2005) observed that riparian fine root productivity dropped sharply with increased riparian deposition caused by anthropogenic disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial and plant dynamics are not well understood in these types of recent deposits. Cavalcanti and Lockaby (2005) observed that riparian fine root productivity dropped sharply with increased riparian deposition caused by anthropogenic disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Buried horizons are often found in Cumulic Regosols, which commonly result from intermittent flooding and deposition (Soil Classification Working Group 1998). Hydroperiod is generally accepted to be the dominant controlling process on forested wetlands (Baker III et al 2001a) and research has shown that hydrological fluctuations can influence fine root turnover (Baker III et al 2001a;Cavalcanti and Lockaby 2005), litter decay rates (Baker III et al 2001b;Shaw et al 2001) and storage of highly stable C in buried horizons (Shaw et al 2001;Blazejewski et al 2005).…”
Section: Shaw Et Al * Stratifying Soils For Soil C Modeling 509mentioning
confidence: 99%
“…While the considered decision contexts are hypothetical, they are realistic both in terms of the types of tools that people are using to assess the ecosystem response for ES assessments, and for the types of regulations and investments ES approaches are being used to support. [Cavalcanti and Lockaby, 2005;Cohen et al, 2006]. Approximately 65% of the base is classified as forest, 17% as range, 6% each as agriculture and wetlands, and 4%…”
mentioning
confidence: 99%